Територіально-адміністративна реорганізація Правобережної України в ході другого і третього поділів Речі Посполитої - Ткачук, Анатолій Петрович; Tkachuk, Anatolii P. (Криворізький державний педагогічний університет, 2004)
Досліджено процес інтеграції до складу Росії та зміни в суспільно-політичному житті та територіально-адміністративному устрої територій Правобережної України. Проаналізовано систему російських органів влади, яка встановлювалася після другого та третього поділів Речі Посполитої. Звернено увагу на зміни в соціальній структурі населення досліджуваного регіону.

The process of integration into Russia and changes in the socio-political life and territorial and administrative structure of the territories of the Right-Bank Ukraine are researched. The system of the Russian authorities, which was established after the second and third divisions of the Commonwealth, was analyzed. The attention is paid to changes in the social structure of the population of the studied region.
Territorial and administrative reorganization of the Right-Bank Ukraine during the second and third divisions of the Commonwealth
Keywords: територіально-адміністративна реорганізація; Правобережна Україна; поділи Речі Посполитої; генерал-губернаторство; інтеграція; territorial and administrative reorganization; Right Bank Ukraine; Divisions of the Commonwealth; Governor General; integration